The Fate of Job in Jewish Tradition: On Job’s counterpointist function - Schleicher, Marianne (Nordisk judaistik/Scandinavian Jewish Studies, 2008)
Job’s piety in The Book of Job is so ideal that it becomes problematic on two levels. First, it renders God a tyrant. Second, no one can fully identify with Job. Surely, we may suffer just as much as Job does and even feel that God is unjust, but no man can ever claim to be as pious as Job. Limited to a few examples of the fate of Job in Jewish tradition and concerned with Scripture’s role with respect to religious normativity, this article will be guided by the following question: How can The Book of Job maintain its role within Jewish tradition as a normative text? My reading suggests that The Book of Job in itself is not normative. Rather, it serves as a counterpoint up against which the reception and transformation of Jewish theology can unfold and as such The Book of Job exerts its function on Jewish religiosity.